Developing authentic assessment: Project assessment on mathematics learning evaluation by using e-learning - Muhammad Jamaluddin; Nailil Faroh (Math Didactic: Jurnal Pendidikan Matematika, 2019)
The standar become a theacher is to have four competencies, these are pedagogic, professional, personality, and social competence. However, there are still some competencies that are not fully mastered in practicing a teaching evaluation. According to that issue, a lecture is supposed to create an instrument evaluation that can be used to describe real students’ pedagogic competency achievement in learning evaluation. One of the assessment principles that can be applied to project authentic assessment by using e-learning. This project assessment is applied in electronic learning in which the students can be helped by electronic media when they finish the project. This study is aimed to create an instrument of project assessment for a class of Mathematics Learning Evaluation System. This study uses the ADDIE development model. The data of this study are expert validation, field observations, and students’ responses. The result obtained from the instrument validation test of project assessment is valid, the practicality of the use of the instrument included in practice category and students’ responses are positive, and instrument reliability is included in the high category, so it can be concluded that the instrument is appropriate to use.